2019
DOI: 10.1002/adem.201901075
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Microstructure and Mechanical Properties of Ti‐43/46Al–5Nb–0.1B Alloys Modified by Mo

Abstract: To improve mechanical properties of TiAl-Nb alloys and obtain effects of Al content on microstructure, Ti-43/46Al-5Nb-0.1B-xMo alloys are prepared. Phase constitution, macro-/microstructure volution, and mechanical properties of them are investigated systematically and compared in detail. Results show that the lamellar colony size refines, B2 phase increases and Al-segregation in interdendritic regions aggravates with the increase in Mo content. The increased B2 phase is attributed to the increased Mo segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Researchers [ 31,32 ] found that the Mo atom in titanium alloys occupies the position of Al or Nb atom in the B2 phase, which causes segregation of Al elements. Figure shows the distribution diagram of the Al element adjacent to the crack of Ti 2 AlNb−2Mo alloy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers [ 31,32 ] found that the Mo atom in titanium alloys occupies the position of Al or Nb atom in the B2 phase, which causes segregation of Al elements. Figure shows the distribution diagram of the Al element adjacent to the crack of Ti 2 AlNb−2Mo alloy.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, under larger loading stress, cracks are easily generated along with the interface of the α 2 /B2 phase and propagate to the substrate of the B2 phase, as shown in Figure 10d,e. Researchers [31,32] found that the Mo atom in titanium alloys occupies the position of Al or Nb atom in the B2 phase, which causes segregation of Al elements. Figure 12 shows the distribution diagram of the Al element adjacent to the crack of Ti 2 AlNbÀ2Mo alloy.…”
Section: Fracture Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the size of the lamellar colony, which is formed by the α grain, was small. From the point of view of the β-stable phase, 1 at.% Mo is equal to 4-6 at.% Nb [2,6,24], so an increase of 0.5 at.% Mo can form more β phase, leading to more pronounced grain refinement. However, the α phase appears in the solid phase transformation path of the TNM alloy, when the Al content exceeds 43.5 at.%, and the α-phase region expands with the increase in Al content.…”
Section: The Influence Of Element On Microstructurementioning
confidence: 99%
“…Although the single-phase alloys offer excellent resistance to environmental attack (oxidation and hydrogen absorption) and initially drew the interest of several researchers, their uttermost lack of ductility and fracture toughness at room temperature, particularly in the binary state rendered them irrelevant for any engineering application [10]. Nevertheless, extensive research has shown that the two-phase (α 2 -Ti 3 Al + γ-TiAl) or multi-phase γ-TiAl based alloys that solidify through the β-phase (i.e., L + β → β) and the α-phase (i.e., peritectic reaction: L + β → α ) with Al composition between 40 and 48 at.% [Ti (40)(41)(42)(43)(44)(45)(46)(47)(48)] have engineering significance [11,12]. These alloys are known as γ-TiAl-based alloys with the γ-(TiAl) and α 2 -Ti 3 Al being the primary and secondary phases, respectively.…”
Section: Introduction 1binary Phase Diagram Of Tial Alloysmentioning
confidence: 99%